On the detectability of the hydrogen 3-cm fine-structure line from the epoch of reionization - Dijkstra, M.; Lidz, A.; Pritchard, J.; Greenhill, L.; Mitchell, D.; Ord, S.; Wayth, Randall (Oxford University Press, 2008)
A soft ultraviolet radiation field, 10.2 < h? < 13.6 eV, that permeates neutral intergalactic gas during the epoch of reionization (EoR) excites the 2p (directly) and 2s (indirectly) states of atomic hydrogen. Because the 2s state is metastable, the lifetime of atoms in this level is relatively long, which may cause the 2s state to be overpopulated relative to the 2p state. It has recently been proposed that for this reason, neutral intergalactic atomic hydrogen gas may be detected in absorption in its 3-cm fine-structure line (2s1/2 ? 2p3/2) against the cosmic microwave background out to very high redshifts. In particular, the optical depth in the fine-structure line through neutral intergalactic gas surrounding bright quasars during the EoR may reach tFS ~ 10-5. The resulting surface brightness temperature of tens of µK (in absorption) may be detectable with existing radio telescopes. Motivated by this exciting proposal, we perform a detailed analysis of the transfer of Lyß, ?, d, ... radiation, and reanalyse the detectability of the fine-structure line in neutral intergalactic gas surrounding high-redshift quasars. We find that proper radiative transfer modelling causes the fine-structure absorption signature to be reduced tremendously to tFS ? 10-10. We therefore conclude that neutral intergalactic gas during the EoR cannot reveal its presence in the 3-cm fine-structure line to existing radio telescopes. © 2008 The Authors.